Design of a motorway in Senegal : towards a multidimensional installation reconciling the development and patrimony - (:unkn) unknown (My University, 2014)
Infrastructure and development seem to go together. However, these two notions challenge a fundamental problem, linked to land management, which must necessarily take into account some of their important impacts on cultural heritage and the environment. The majority of African countries, particularly in sub-Saharan Africa, are facing rapid changes in their major cities-an evolution sometimes anarchic. The city of Dakar, established during the colonial period, is a case in point with its deficiencies in terms of mobility increased by pressure on available land. To mitigate or relieve this situation of asphyxia within the city of Dakar, the State of Senegal decided to develop an economic zone not far from the capital as well as heavy transport infrastructure such as the Dakar-Diamniadio turnpike. This thesis examines both different modes of governance and the trajectories of transport infrastructure, particularly roads, in Senegal. In so doing, it examines the hybridization of land development and the politics of heritage in the broadest sense of the term. Moreover, this thesis analyzes the different social processes related to the construction and then the commission of this new technical object.
Keywords: African Research